Models of Education: In-Depth Review - S. F., Sagimin; Muhammad Nubli, Abdul Wahab (SERSC, 2015)

(untitled)
The information in this review provides comparative assessments of major educational models currently being used worldwide. The purpose of this literature review is to develop a frame of reference for both models of education and that of teacher self-efficiency using relevant research studies to illuminate the possible relationship between these two variables. To serve its purpose, this paper will cover some types of educational models and will be designated as part 1. Part 2 will thus be covered in future manuscript. In short, this article focuses on two variables-education techniques or models and their implementer, i.e. the teacher.